IMPLEMENTASI MODEL PEMBELAJARAN HABIT FORMING DALAM PEMBENTUKAN KEPRIBADIAN HOLISTIC MELALUI PEMBELAJARAN AQIDAH AKHLAK DI SEKOLAH ADIWIYATA MI AL-FALAH KUNCUNG BANYUARANG NGORO JOMBANG - Eni Nur Anisah; Evita Widiyati (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2020)
School is one of the educational institutions that organizes the teaching and learning process to guide, educate, train and develop student’s abilities to achieve educational goals, including human character at MI Al-Falah Kuncung there is a habit, especially in carrying out daily habits. The focus of research on this thesis is as follows is the implementation of the habit forming learning model in the adiwiyata school MI Al-Falah Kuncung Banyuarang Ngoro Jombang and the holistic personality of the fourth grade personality of the fourth grade students at MI Al-Falah Kuncung Banyuarang Ngoro Jombang adiwiyata school. The approach in this research uses a qualitative approach with a descriptive type. The research setting took place at MI Al-Falah Kuncung Banyuarang Ngoro Jombang. Meanwhile the data sources are teachers of aqidah morals, classroom teachers, students, and directors. Way of unifying data using interviews, observation, and archiving. The research results obtained by the researcher are as follows the application of the habit forming learning model starting from (the habit formation model sequence) the steps of habit forming in students habits are carried out continuously and someone or role model, and a holistic personality what is seen in grade IV students is that they are able to apply moral behavior, and also position their behavior as a student, but they have not been able to control their own behavior, this can be seen from the attitudes of some students when learning aqidah morals takes place they do not concentrate and tend not to pay attention to the teacher.